Los Libros de Medicina en el Chile del Siglo Xviii: Tipologías, Propietarios y Dinámicas de Circulación - Labarca-Pinto, M (Universidad Nacional de Colombia, 2020)
The objective of the article is to provide an account of the analytical possibilities deriving form the study of the medical books that circulated in Chile during the 18th century. On the basis of the study of private library inventories, commercial inventories, and customs documents, it explores the links between the availability of titles and the tastes of owners/readers. To that effect, it identifies the main characteristics of the medical books that circulated in Chile, and then goes on to examine the profiles of their owners, the possible uses of those books, and their connection to the dynamics of trade flows. The article shows the visibility acquired by medical books, and suggests that the availability of titles was not merely subordinated to commercial flows, but was also determined by the owners, who played an active role in constituting themselves as a specific reading audience and creating alternative access routes. © 2020 Universidad Nacional de Colombia. All rights reserved.